PENGARUH SELF ASSESSMENT SYSTEM, PENERBITAN SURAT TAGIHAN PAJAK DAN PENAGIHAN PAJAK DENGAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI PADA KPP MADYA DAN KPP PRATAMA TAMPAN PEKANBARU - Sitio, Rohmasari; Basri, Yesi Mutia; Paulus, Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Proceeds from taxation sector is the largest source of state revenue. There are many factors that can affect the amount of tax receipts especially VAT receipts which can be considered the tax general directorate in making a policy. This study aims to examine the effects of the independent variables (PKP registered, SSP VAT, VAT return period reported, STP VAT and SP VAT) on the dependent variable (Value Added Tax receipt) with partial test. The data obtained for this study came from the Tax Service Office Madya Pekanbaru and Tax Service Office Pratama Tampan Pekanbaru, including number registered PKP, the amount deposited by the SSP VAT, the amount of the VAT return period reported by PKP, the amount of STP VAT and SP VAT issued by the tax authorities and the amount of VAT receipts. The method used in this research is descriptive statistical methods. The sampling method using sampling methods saturated, whereas the type of data used are secondary data with monthly data unit for 4 years so it amounted to 48 pieces, once the data is collected, the data were analyzed using SPSS 20.0 for windows. The data were analyzed to test the hypothesis using multiple linear regression analysis approach.. The research results are as follows: (1) The number of registered PKP and CNS VAT effect on VAT receipts. (2) The amount of time the VAT tax return does not affect the VAT receipts. (3) STPs and Forced report VAT has no affect the VAT receipts.The capability of independent variables explain Value Added Tax Receipts of 78,1% and the remaining 21,9% is influenced by other variables.Keywords: Self Assessment, tax claim, force report,Value Added Tax receipt.